Hubungan Keterampilan Berbicara dengan Pola Asuh pada Anak Usia Dini di Desa Lau Kecamatan Dawe - Dyah Ayu Setyo Astuti; Salma Arsyadani Noor Azha; Sazkia Indah Putri; Latifatul Asna; Luthfa Nugraheni (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
Speaking ability is an important aspect of early childhood language development. Speech delay is experienced by many children so that it has an impact on children's social, emotional, and cognitive development. The parenting style of parents is one of the main factors that also affect the presence of speech delays. These delays can be caused by a number of improper parenting, especially during early childhood development. This study aims to analyze the parenting relationship of parents. Delay in talking to a child is a major focus in the analysis. The qualitative descriptive method is a method used with a focus on the analysis of permissive, authoritarian, democratic parenting of children aged 4 and 5 years. The results of the study are expected to provide a clearer picture of the influence of parenting on the development of children's speech skills and become the basis for education for parents in implementing appropriate parenting.